Involuntary affinities. - Edwards, George (Southwest Review, 1990)
Presents the composer-author's observations on the changes in western music and performance in the 20th century. Western music's willingness to sacrifice many minute distinctions of pitch and rhythm; Compromise made by tuning systems; Concept of meter; Preference for clear boundaries; Nature and pacing of the ending; Emphasis on thematic relations and tone color.